Development of Over-Scheduled Scale for Adolescents - Tany, Rajeka Fardosh; Khanam, Mahfuza (Dhaka University Journal of Biological Sciences, 2023)
The purpose of the present study was to develop a scale to measure overscheduling of the adolescents in Bangladesh. 51 items were initially constructed. This scale was divided into seven sub divisions. Those are the mood (7 items), academic grade (7 items), favorite activities (8 items), sleep (5 items), food habit (9 items), withdrawal behavior (8 items) and physical illness (7 items). These items were arranged in a 4-point Likert type scale for the first try out. It was administered 119 adolescents who are purposively selected. Among them 58 were overweight adolescents (30 boys and 28 girls) and 61 were normal weight adolescents (31 boys and 30 girls). The age range of the participants are 11 to 16 years. To determine the internal consistency item-total correlation and Cronbach’s Alpha was calculated. The Cronbach’s Alpha of total scale was .869 and sub scales were also satisfactory, α =0, 01. Content validity, convergent validity and concurrent validity were calculated and those were also found significant for overscheduled scale for adolescents. The minimum and maximum possible score of this scale was 0 to 144. Higher scores indicate high level of over schedule and lower score indicate less level of over schedule. Dhaka Univ. J. Biol. Sci. 31(2): 231-242, 2022 (July)